Role of Tc-99m sestamibi SPECT/CT myocardial perfusion imaging in management of spontaneous coronary artery dissection: A case report - Shelvin Kumar Vadi; Deepa Singh; Ashwani Sood; Ajay Bahl; Madan Parmar; Bhagwant Rai Mittal (IHJ Cardiovascular Case Reports, 2018)
Spontaneous coronary artery dissection (SCAD) is a rare sporadic disorder of abrupt dissection in the coronary arteries resulting in impaired perfusion to the myocardium. The authors present two cases of SCAD where myocardial perfusion imaging (MPI) done for assessment of myocardial viability helped in deciding the definitive management.